2021
DOI: 10.3390/su13063155
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Different Tillage Practices on Soil Water Infiltration for Sustainable Agriculture

Abstract: Over the years, cultivation using sustainable tillage practices has gained significant importance, but the impact of tillage on soil water infiltration is still a concern for landowners due to the possible effects on crop yield. This study investigates the impact of different tillage managements on the infiltration rate of sandy clay loam soil under a semiarid environment. Field experiments were conducted in Chott Mariem Sousse, Tunisia. The tillage practices consisted of three treatments, including a tine cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 48 publications
6
22
1
Order By: Relevance
“…Since the infiltration experiments were conducted between 7 MAP and 10 MAP, and given the relatively high clay content of the soil, settlement of particles [59], lower porosity and closed-pore openings may account for the low initial and basic infiltration rates in the plough-till plots. e infiltration rate under no-tillage and conventional tillage systems estimated by Amami et al [31] also disagrees with our study. ey found that, in the order of mouldboard plowing, tine cultivation, and no tillage, the investigated sandy clay loam soil's infiltration capacity was reduced.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Since the infiltration experiments were conducted between 7 MAP and 10 MAP, and given the relatively high clay content of the soil, settlement of particles [59], lower porosity and closed-pore openings may account for the low initial and basic infiltration rates in the plough-till plots. e infiltration rate under no-tillage and conventional tillage systems estimated by Amami et al [31] also disagrees with our study. ey found that, in the order of mouldboard plowing, tine cultivation, and no tillage, the investigated sandy clay loam soil's infiltration capacity was reduced.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, Lindstrom and Onstad [28] found infiltration to be slower in soils under conservation tillage practices because these soils were denser or less susceptible to crust disturbance. Other studies have demonstrated that no-till, compared to ploughed soil, had higher infiltration rates (as in [29] and as similarly reported by [30]) or lower infiltration rates (as observed by [31]). Nonetheless, weed control is a very important aspect of any crop production enterprise.…”
Section: Introductionsupporting
confidence: 75%
“…K fs increases with the impact of agricultural practices (Figure 3a), which may point to the practice of tillage. Soil tillage can increase porosity and decrease bulk density, thereby increasing infiltration rates (Amami et al, 2021). However, soil tillage may also decrease SOC and aggregate stability which negatively affects soil infiltrability (Sithole et al, 2019).…”
Section: Effect Of Land Usementioning
confidence: 99%
“…Greater leaching of salt under NT is unlikely. Water infiltration measurements carried out at the same site showed higher infiltration under CT and MT than NT (Amami et al, 2021). Qingjie et al (2014) also reported a significant decrease in EC under NT relative to conventional tillage with plowing.…”
Section: Responses Of Soil Chemical Quality Indicators To Tillage Man...mentioning
confidence: 86%
“…The study was carried out at the experimental station of the Technical Center of Organic Farming (TCOF) located in Sousse region, Eastern Tunisia (35°55'12.82"N; 10°34'00.51''E). The climate is Mediterranean, semi-arid, with mean annual air temperature of about 17.5°C and with mean annual precipitation of 400 mm, most of which is received during winter Amami et al (2021). The soil is classified as Fluvisol (IUSS Working Group WRB 2015).…”
Section: Study Site and Soil Samplingmentioning
confidence: 99%